2007
DOI: 10.1103/physrevb.76.155104
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofLaNiO3x: Anin situsoft x-ray photoemission and absorption study

Abstract: We investigate the electronic structure of high-quality single-crystal LaNiO3 (LNO) thin films using in situ photoemission spectroscopy (PES). The in situ high-resolution soft x-ray PES measurements on epitaxial thin films reveal the intrinsic electronic structure of LNO. We find a new sharp feature in the PES spectra crossing the Fermi level, which is derived from the correlated Ni 3d eg electrons. This feature shows significant enhancement of spectral weight with decreasing temperature. From a detailed analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 37 publications
9
35
1
Order By: Relevance
“…27 The e g states (a) are clearly resolved as a sharp peak at the Fermi level and the strong t 2g peak is located at 1.0 eV below the Fermi edge. The O 2p states (c), located below the t 2g states, correspond to non-bonding O 2p states, as their hybridization with the Ni 3d states is restricted by symmetry.…”
Section: Electronic Structure and Experimental Energy Spectramentioning
confidence: 99%
“…27 The e g states (a) are clearly resolved as a sharp peak at the Fermi level and the strong t 2g peak is located at 1.0 eV below the Fermi edge. The O 2p states (c), located below the t 2g states, correspond to non-bonding O 2p states, as their hybridization with the Ni 3d states is restricted by symmetry.…”
Section: Electronic Structure and Experimental Energy Spectramentioning
confidence: 99%
“…They confirmed that charge carriers in bulk LaNiO 3 contain considerable oxygen character, and they related the MIT to the disappearance of charge carriers. Horiba et al 38 performed x-ray photoemission spectroscopy (XPS) and XAS of LaNiO 3−δ thin films and found that the density of states near the Fermi level in these films is very sensitive to oxygen content. They also performed firstprinciples calculations of bulk LaNiO 3 under strain and found that strain alone cannot explain the experimentally observed narrowing of the Ni 3d e g peak at the Fermi level.…”
Section: -36mentioning
confidence: 99%
“…By using this system, one can perform in situ SRPES study of transition metal oxide thin films and obtain the PES data reflecting the intrinsic electronic state of TMOs. 17,18 It will be interesting to apply the in situ SRPES measurements to VO 2 /TiO 2 (001) for the purpose of obtaining the intrinsic electronic states of the VO 2 thin films and valuable information on the origin of the insulating behavior in the VO 2 thinner films.…”
Section: Introductionmentioning
confidence: 99%